Treatment of arterial hypertension in metabolic syndrome in men with erectile dysfunction - S. V. Nedogoda; A. S. Salasyuk; I. N. Barykina; A. A. Ledyaeva; V. V. Tsoma; E. V. Chumachek (Медицинский совет, 2013)
Metabolic syndrome (MS) is a combination of hormonal, metabolic and clinical disorders, and one of the most studied subjects in the modern medicine. Today MS is considered to be a major risk factor for cardiovascular disease, disorders of carbohydrate metabolism and pathology of the reproductive system [6, 41].